SQLE facilitates the pancreatic cancer progression via the lncRNA‐TTN‐AS1/miR‐133b/SQLE axis. Issue 13 (31st May 2022) - Wang, Shuhui; Dong, Lei; Ma, Lin; Yang, Suzhen; Zheng, Ying; Zhang, Jing; Wu, Chuanghong; Zhao, Yidi; Hou, Yangfan; Li, Hong; Wang, Ting
Abstract: Studies have shown that SQLE is highly expressed in a variety of tumours and promotes tumour progression. However, the role of SQLE in pancreatic cancer (PC) has not been reported. Here, we aim to study the role and molecular mechanism of SQLE in PC. Immunohistochemistry and functional experiments showed that SQLE was highly expressed in PC tissues and promoted the proliferation and invasion of PC cells. Terbinafine, an inhibitor of SQLE, inhibited this effect. In order to further study the upstream mechanism that regulates SQLE, we used bioinformatics technology to lock miR‐133b and lncRNA‐TTN‐AS. In situ hybridization was used to detect the expression of miR‐133b and lncRNA‐TTN‐AS1 in PC tissues. The luciferase reporter gene experiment was used to confirm the binding of miR‐133b and lncRNA‐TTN‐AS1. The results showed that miR‐133b was down‐regulated in PC tissues and negatively correlated with the expression of SQLE. LncRNA‐TTN‐AS1 was upregulated in pancreatic cancer tissues and positively correlated with the expression of SQLE. Luciferase gene reporter gene analysis confirmed lncRNA‐TTN‐AS1 directly binded to miR‐133b. Therefore, we propose that targeting the lncRNA‐TTN‐AS1/miR‐133b/SQLE axis is expected to provide new ideas for the clinical treatment of PC patients.